1982
DOI: 10.1111/j.1559-1816.1982.tb00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Control‐Related Problems at Three Mile Island1

Abstract: The relationship between stress and control for residents at Three Mile Island (TMI) was examined. TMI was studied because of the technological nature of the accident there. Residents of Frederick, Maryland, more than 80 miles from TMI, were used as a comparison group. Control‐related problems were measured using questionnaires and a behavioral task. Stress levels were determined using self‐report, behavioral, and biochemical measures. Residents at TMI reported more loss of control and performed more poorly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…Consistent with previous research at TMI showing that symptoms of stress were inversely related to perceived control, TMI area residents who reported more perceived control over their lives tended to exhibit lower levels of urinary cortisol. Loss of control has been associated with depression and changes in adrenal activity (28,29) and may play an important role in translating the effects of uncertainty into chronic stress. The relationship between control and hormonal response to stress awaits further testing.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research at TMI showing that symptoms of stress were inversely related to perceived control, TMI area residents who reported more perceived control over their lives tended to exhibit lower levels of urinary cortisol. Loss of control has been associated with depression and changes in adrenal activity (28,29) and may play an important role in translating the effects of uncertainty into chronic stress. The relationship between control and hormonal response to stress awaits further testing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to measures of stress symptoms, we asked subjects about feelings of helplessness and whether they felt as though they had control over what happened to them. Subjects rated these feelings on likert-type scales and clear differences between TMI and control groups were found (45). Perceived control was a significant mediator of stress responding 17 months after the accident (45], and examination of ratings of helplessness and control over the course of the study indicated that differences persisted well beyond this 1980 assessment (Figure 3).…”
Section: Controlmentioning
confidence: 96%
“…Conclusions of the above studies showed how distance affects residents' attitude towards the NIMBY facilities. Several studies showed that people who lived near the nuclear power plant of Three Mile Island had stronger stress reactions than people who lived far away [53,54]. Huppe and Weber [52] found an inverted U-shaped relationship between the strength of opposition towards nuclear power plants and the distance of dwelling place to the plant.…”
Section: Methods Of Testing the Nimby Syndromementioning
confidence: 99%